FROP-1 peptide-conjugated ultrasmall superparamagnetic nanoparticles as a targeted T1-weighted MR contrast agent for breast cancer: in vitro study - Melika Samari; Zahra Alamzadeh; Rasoul Irajirad; Abolfazl Sarikhani; Vahid Pirhajati Mahabadi; Habib Ghaznavi; Samideh Khoei (BMC Biomedical Engineering)
Abstract Background The aim of this study was to produce ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles (NPs) conjugated to the FROP-1 peptide for targeted magnetic resonance imaging (MRI) of breast cancer cell lines and to evaluate its application as a specific and targeted T1-weighted MR imaging contrast agent in vitro. Sodium citrate-stabilized Fe3O4 NPs were conjugated with the FROP-1 peptide by 1-ethyl-3-(3-dimethylaminopropyl) carbide diamide hydrochloride (EDC) to form a novel Fe3O4@FROP-1 specific target contrast agent. The specificity and targeting of Fe3O4@FROP-1 to bind FROP-1 receptors were investigated in vitro by cellular uptake and cellular MR imaging. Results In this study, the synthesis of water-soluble ultrasmall Fe3O4 NPs was performed by the co-precipitation method. XRD, TEM, and VSM analyses showed the formation of the Fe3O4 NPs with an average size of about 3.78 ± 0.2 nm. FT-IR spectroscopy approved the conjugation of the FROP-1 peptide with the Fe3O4 NPs. The synthesized Fe3O4@FROP-1 NPs showed good biocompatibility, and the high r1 relaxivity and r2/r1, respectively, were 2.608 mM− 1S− 1 and 1.18. The biocompatibility of the Fe3O4 and Fe3O4@FROP-1 NPs on the MCF-7, SKBR-3, MDA-MB-231, and MCF-10 cell lines was determined using cytotoxicity analysis. The specific targeting effect on the cells was verified by in vitro cellular uptake and cell MR imaging. Conclusion It was found that the contrast intensity of the Fe3O4@FROP-1 nanoprobe increases as Fe concentration increases. Cellular uptake of the Fe3O4 and Fe3O4@FROP-1 NPs was quantified using ICP-MS. The synthesized NPs had better imaging performance than Dotarem (gadoterate meglumine). The findings showed that Fe3O4@FROP-1 NPs have potential utility as a specific and targeted T1-weighted contrast agent in breast cancer MR imaging. Graphical Abstract